The Influence of Store Atmosphere, Service Quality and Hedonic Shopping Value on Purchasing Decisions at Kwangya Store Jakarta with Emotion as a Mediating Variable - Sari, Anisya Permata; Barkah, Barkah; Ramadania, Ramadania (Universitas Pahlawan Tuanku Tambusai, 2024)
The development of the kpop industry has resulted in the development of stores selling kpop merchandise. This research aims to determine the influence of store atmosphere, service quality and hedonic shopping value on emotional purchasing decisions as mediation at Kwangya store Jakarta. This research is quantitative research. The population in this study were visitors to the Kwangya store Jakarta. The sample in this study amounted to 250 respondents. Sampling was carried out using a non-probability sampling method in the form of purposive sampling. The data collection technique was carried out using a questionnaire via Google Form. Data processing in this research uses SmartPLS version 4 software. The results of this research show that store atmosphere has a positive and significant effect on purchasing decisions; service quality has a positive and significant effect on purchasing decisions; hedonic shopping value has a positive and significant effect on purchasing decisions; shop atmosphere has a positive and significant effect on emotions; service quality has a positive and significant effect on emotions; emotional influence is positive and significant on purchasing decisions; store atmosphere has a positive and significant effect on purchasing decisions through emotion as mediation; Service quality has a positive and significant effect on purchasing decisions through emotion as mediation.